Spatial elements that create the quality public space - Fejza, Adelina (Igra ustvarjalnosti, 2022)
Public space is an essential element of human wellbeing and the overall development of the city and society. This paper presents a brief outlook of the past and present situations related to the planning and use of public spaces in urban environments. In doing so, this paper addresses the fi nding that public spaces gradually lose the focus of quality in them, and as time goes by, these spaces are reshaping even in human-unfriendly places. The purpose of this presented research is to fi nd out what are the key elements that create a quality public space. To achieve it, it is used a comparative–descriptive method comparing two relevant pieces of literature or authorial approaches, Henaff and Strong's “Public Space and Democracy” and Pérez-Gómez's “Attunement”. These two examples fulfi ll the criteria of having diff erent interdisciplinary approaches toward public space, explained through diff erent periods and backgrounds. It is found that the crucial elements these authors suggest for building qualitative space are well-grounded. As such, they can be implemented in an integrated physical form because they base on the human factor or the physical presence and experience in space. In the conclusion part, a suggestion was made to include these elements in the process of planning and designing public spaces in the context of the challenges of modern living culture.
Keywords: človeški faktor; human factor; javni prostor; kakovosten javni prostor; key elements; ključni elementi; public space; quality public space; urban planning and design; urbanistično načrtovanje in oblikovanja